2017
DOI: 10.3390/ma10111298
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Modified Polyvinyl Chloride for Removal of Thionine Dye (Lauth’s Violet)

Abstract: The chemical modification of hydrophobic polymer matrices is an alternative way to elchange their surface properties. The introduction of sulfonic groups in the polymer changes the surface properties such as adhesion, wettability, catalytic ability, and adsorption capacity. This work describes the production and application of chemically modified polyvinyl chloride (PVC) as adsorbent for dyes removal. Chemical modification of PVC was evaluated by infrared spectroscopy and elemental analysis, which indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…On other hand, NC has a semicrystalline nature. 35,36 Figure 3(a) shows the XRD diffractogram of pure PVC. The main diffraction peaks are observed at 2⊔ = 29.5°, 25.1°and 39.63°of PVC which is in good agreement with recent reports.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On other hand, NC has a semicrystalline nature. 35,36 Figure 3(a) shows the XRD diffractogram of pure PVC. The main diffraction peaks are observed at 2⊔ = 29.5°, 25.1°and 39.63°of PVC which is in good agreement with recent reports.…”
Section: Resultsmentioning
confidence: 99%
“…Other reports concluded that commercial PVC is primarily an amorphous glassy polymer with a small percentage of crystalline structure and is therefore referred to as semicrystalline. On other hand, NC has a semicrystalline nature 35,36 . Figure 3(a) shows the XRD diffractogram of pure PVC.…”
Section: Resultsmentioning
confidence: 99%
“…The Brunauer–Emmett–Teller (BET) was exploited to display the N 2 loading and desorption on PVC, PVC‐MG, and PVC‐MG‐NMDG. From Table 2, the specific pore volume V (cm 3 g −1 ), surface area σ BET (m 2 g −1 ), and average pore diameter d (nm) of PVC were 0.0021 cm 3 g −1 , 0.27 m 2 g −1 , and 6.59 nm 55 . When amination was performed by methyl glycinate to form PVC‐MG, the pore volume and surface area increased to 0.248 cm 3 g −1 and 170.8 m 2 g −1 , while the diameter of the typical pore (average pore diameter) decreased to 5.56 nm.…”
Section: Resultsmentioning
confidence: 99%
“…From Table 2, the specific pore volume V (cm 3 g À1 ), surface area σ BET (m 2 g À1 ), and average pore diameter d (nm) of PVC were 0.0021 cm 3 g À1 , 0.27 m 2 g À1 , and 6.59 nm. 55 When amination was performed by methyl glycinate to form PVC-MG, the pore volume and surface area increased to 0.248 cm 3 g À1 and 170.8 m 2 g À1 , while the diameter of the typical pore (average pore diameter) decreased to 5.56 nm. Moreover, the condensation reaction between PVC-MG and N-methyl-D-gluconate resulted in the formation of a PVC-MG-NMDG composite with an enhancement in both specific pore volumes (0.319 cm 3 g À1 ) and surface area (217 m 2 g À1 ), while vanishing in average pore diameter to 4.73 nm.…”
Section: Brunauer-emmett-teller (Bet) Analysismentioning
confidence: 99%
“…Similarly, Soman et al [24] found that the C-Cl peak appeared between 613 and 615 cm -1 [25]. Additionally, the characteristic absorption bands assigned to the C-Cl stretching vibration are observed in the region between 700 and 600 cm -1 [26-28], particularly at 683 and 611 cm -1 [29][30][31]. Moreover, the aromatic group of styrene is visible in these spectra in self-and chemical crosslinking.…”
Section: Ftir Of Pvc/sbr Membranesmentioning
confidence: 91%